Redescription and phylogenetic assessment of Barbadocladius andinus Cranston & Krosch (Diptera: Chironomidae) from the Patagonian Andes - Donato, Mariano; Mauad, Melina; Viegas, Vanesa S. Marin; Siri, Augusto (Zootaxa, 2026)
Barbadocladius is a genus of orthoclad midges endemic to the Andes, currently comprising two described species: B. andinus and B. limay. In this study, we emend the diagnosis of the genus. The male, female, and pupa of B. andinus and the pupa of B. limay are redescribed based on new material from the Patagonian Andes. Morphological analyses exhibited the expected variation typical of pupal traits, while mitochondrial COI sequences showed marked genetic divergence between Patagonian and Peruvian populations. Phylogenetic and NMDS analyses do not indicate a latitudinal genetic structure, but possible cryptic diversity or incipient speciation events are suggested. The absence of intermediate samples limits conclusions about the nature of this divergence. Further integrative studies are needed to clarify the taxonomy and evolutionary history of the genus. Beyond the taxonomic revision, this work provides an example of a population-level genetic analysis in a non-charismatic, non-economically relevant insect group. Such studies are usually restricted to taxa of agricultural, quarantine, or conservation concern. By applying integrative tools to Barbadocladius, we highlight how combining molecular and morphological evidence can reveal hidden diversity even in poorly known, non-model lineages, contributing to a broader understanding of Andean biogeography and evolutionary processes.